Advancing Computational Approaches for Geometry Optimization of Steel Structures - LAX, Artur; MILEWSKI, Sławomir (Engineering Transactions, 2024)
The primary objective of this study is to develop and assess computational methods for optimizing the geometry of specific building structures modeled through parametric description. The focus is on steel bar structures, including trusses and beams, subjected to varying load conditions with fixed and uncertain parameters. The decision variables in the single- or multicriteria non-linear optimization problem correspond to selected geometric features of these structures. The proposed methodology revolves around dividing the entire construction into distinct structural patterns. This allows for addressing separate local optimization problems with a reduced number of decision variables, followed by a global optimization consideringthe interactions between these patterns. This approach is versatile, serving both the design of objects meeting required architectural and structural conditions and constraints, and the optimization of all or specific parameters, incorporating diverse economic (e.g., material usage) and engineering criteria (e.g., limit states).